Sea bream (Sparus auratus) estrogen receptors: phylogeny and tissue distribution - Pinto, Patricia IS (2014)
Most estrogen actions are mediated by two estrogen receptor subtypes (ER and ER ). While a single ER appears to be present in higher vertebrates, two forms of ER encoded by different genes have recently been isolated in some teleost fish species. We investigated whether this also applies to the hermaphrodite sparid sea bream (Sparus auratus) and cloned a second ER (sbER 2) in this species. We have also compared the tissue distribution of the three receptors as yet identified in sea bream, designated sbER , sbER 1, and sbER 2.